Capturing photons with transformation optics - Luo, Yu (2015)
Metallic objects in close contact and illuminated by light show spectacular enhancements of electromagnetic fields, due to excitation of surface plasmons, which have potential for exploitation in ultra sensitive spectroscopy and in nonlinear phenomena. They also play a role in Van der Waals forces, heat transfer, and non contact friction. The extremes of length scales, varying from the micron to the sub nano, challenge direct computational attack. Here we show that the new technique of transformation optics enables an analytic approach which offers both physical insight and easy access to quantitative analysis. For two metal spheres at various separations we present details of the new technique, discuss the optical absorption spectrum, spatial distribution of the modes, and the Van der Waals forces.